2010
DOI: 10.1177/0040517510365949
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies of Non-Aqueous Volatiles in Lint Cotton Moisture Tests by Thermal Methods

Abstract: The standard test methods for moisture in lint cotton are based on oven drying at 105—110°C. All of the loss in weight is attributable to moisture. The U.S. cotton industry questions the reliability of the oven-drying method due to the concern that non-aqueous volatiles released during drying may be of an amount sufficient to bias the results. Our approach in these initial studies was to conduct a series of probing experiments to help understand the nature of the non-aqueous volatiles. Cottons were assayed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Considering the amount of weight loss of oven-dried cottons is approximately 7.5% for 10 g of cotton, the average weight lost is 0.75 g. The weight loss observed on the taped slides amounts to approximately 0.24% of the 0.75 g of cotton weight loss, or roughly half of the difference seen between KFT and the oven as has previously been reported. 2,3 In addition, NAV components observed in earlier studies 2,3 and cellulose oxidation may also contribute to the observed bias in moisture contents determined by the KFT and SOD methods, although the quantitative amounts of each of these contributors are still unknown.
Figure 6.Particulate and fibrous matter captured on a greased slide placed on top of cotton balls contained in a weighing bottle placed in an airflow oven heated to 105℃.
Figure 7.Particulate and fibrous matter captured on a greased slide placed on top of cotton from crop year 2001 contained in a weighing bottle placed in an airflow oven heated to 105℃.
Figure 8.Particulate and fibrous matter captured on a greased slide placed on top of cotton from crop year 2007 contained in a weighing bottle placed in an airflow oven heated to 105℃.
…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Considering the amount of weight loss of oven-dried cottons is approximately 7.5% for 10 g of cotton, the average weight lost is 0.75 g. The weight loss observed on the taped slides amounts to approximately 0.24% of the 0.75 g of cotton weight loss, or roughly half of the difference seen between KFT and the oven as has previously been reported. 2,3 In addition, NAV components observed in earlier studies 2,3 and cellulose oxidation may also contribute to the observed bias in moisture contents determined by the KFT and SOD methods, although the quantitative amounts of each of these contributors are still unknown.
Figure 6.Particulate and fibrous matter captured on a greased slide placed on top of cotton balls contained in a weighing bottle placed in an airflow oven heated to 105℃.
Figure 7.Particulate and fibrous matter captured on a greased slide placed on top of cotton from crop year 2001 contained in a weighing bottle placed in an airflow oven heated to 105℃.
Figure 8.Particulate and fibrous matter captured on a greased slide placed on top of cotton from crop year 2007 contained in a weighing bottle placed in an airflow oven heated to 105℃.
…”
Section: Resultsmentioning
confidence: 95%
“…As reported in previous research, differences were noted between moisture measurements determined by KFT and oven drying methods. 2,3 In order to understand these differences, several avenues were explored. One such technique was determining if particulate matter was released during SOD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations